Innovative Teaching Governance and Teacher Performance in Special Region of Yogyakarta and Antecedent Factors - Heri Kurnia; Reza Widhar Pahlevi; Rinaldi; Intan Kusumawati (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2022)
This study aims to determine the role of green information technology and learning orientation as predictors of influencing teacher performance and innovative teaching governance. And to find out the role of the innovative teaching governance construct as a predictor of influencing teacher performance. The population of this research is all teaching staff at State High Schools/Vocational High Schools in Indonesia. The sampling technique used was non-probability simple random sampling with the distribution of questionnaires using google form and a completely filled out questionnaire totaling 183 teaching respondents. The analytical tool used is SEM AMOS. The results showed that there was a significant effect of green information technology and learning orientation on innovative teaching governance; green information technology and innovative teaching governance have been proven to have a significant effect on teacher performance, but learning orientation has no effect on teacher performance.